Infradiaphragmatic total anomalous pulmonary venous connection to portal vein. Diagnostic implications of echocardiography. Issue 6 (June 1977) - Mortera, C; Tynan, M; Goodwin, A W; Hunter, S
Abstract : A case of total anomalous pulmonary venous connection to the portal vein is described. The diagnosis was suspected clinically, supported by the echocardiogram, and confirmed by cardiac catheterisation, angiocardiography, and contrast echocardiography. An echo-free space lying behind the left atrium initially was thought to represent the common pulmonary vein. However, contrast echocardiography showed that this space was not the anomalous vein but probably an artefact. This paper shows that the origins of intracardiac echoes cannot always be assumed from a simple comparison of echocardiography with angiocardiographic or necropsy findings. In some cases it is necessary to introduce a marker into the echocardiogram which unequivocally originates from, and, therefore, localises, the structure under examination. Contrast echocardiography provides such a marker.